Pengembangan Parameter Penilaian Keamanan Pelayanan Kesehatan Tradisional Empiris - Ondri Dwi Sampurno; Nurhayati Nurhayati; Delima Delima; Lucie Widowati; Hadi Siswoyo (Media Penelitian dan Pengembangan Kesehatan, 2020)
Abstract In the context of protecting the community against the security of traditional empirical health services, more detailed safety assessment parameters have been developed for the traditional health aspects (Hattra), methods of care and facilities. Each safety assessment parameter is equipped with an operational definition and tested for validity and tested for reliability to provide objective safety assessment results and consistent assessment results. The development of traditional empirical health service safety assessment parameters is carried out with a quantitative approach. Safety parameters refer to the Minister of Health Regulation (PMK) number 61 of 2016 concerning Traditional Empirical Health Services which includes aspects of Hattra, Methods of Care and Facilities. The number of parameter items in each aspect, namely 6, 27, and 16. The number of parameter items on the aspect of methods of care is divided into 11 items of methods of skills care and 16 items of methods of herbs care. Each parameter item is accompanied by an operational definition for uniformity of perception. Each parameter item is given a score based on a Likert scale (5 = strongly agree; 4 = agree; 3 = neutral; 2 = disagree; 1 = strongly disagree) for evaluating the validity and reliability of 36 people (the number to meet normality) health service experts traditional. Experts come from universities and the Traditional Health Association. Data analysis using SPSS program. Validity analysis using Product moment from Karl Pearson and reliability analysis using Cronbach alpha. The results of the validity test showed that 2 of the 6 parameter items in the Hattra aspect are valid, 26 items out of the 27 parameter items in the aspect of the treatment method are valid, and all items of 16 parameters in the aspect of the tool are valid. Reliability test showed reliable results. The development of traditional empirical health service safety assessment parameters produced reliable parameters and most of the parameters are valid. Invalid parameters are mostly adjusted by sentence without changing the meaning. Abstrak Dalam rangka perlindungan masyarakat terhadap keamanan pelayanan kesehatan tradisional empiris, dikembangkan parameter penilaian keamanan yang lebih terperinci terhadap aspek penyehat tradisional (Hattra), cara perawatan dan sarana. Setiap parameter penilaian keamanan dilengkapi dengan definisi operasional dan diuji validitas serta diuji reliabilitasnya untuk memberikan hasil penilaian keamanan yang obyektif dan hasil penilaian yang konsisten. Pengembangan parameter penilaian keamanan pelayanan kesehatan tradisional empiris dilakukan dengan pendekatan kuantitatif. Parameter keamanan mengacu pada Peraturan Menteri Kesehatan (PMK) nomor 61 Tahun 2016 tentang Pelayanan Kesehatan Tradisional Empiris yang mencakup aspek Hattra, Cara Perawatan dan Sarana. Jumlah item parameter pada masing masing aspek, yaitu berturut-turut 6, 27, dan 16. Jumlah item parameter pada aspek Cara Perawatan terbagi menjadi 11 item Cara Perawatan Keterampilan dan 16 item Cara Perawatan Ramuan. Setiap item parameter disertai dengan definisi operasional untuk keseragaman persepsi. Setiap item parameter diberikan skor berdasarkan skala Likert (5=sangat setuju; 4=setuju; 3=netral; 2=tidak setuju; 1=sangat tidak setuju) untuk evaluasi validitas dan reliabilitas terhadap 36 orang (jumlah untuk memenuhi normalitas) pakar pelayanan kesehatan tradisional. Pakar berasal dari perguruan tinggi dan Asosiasi Penyehat Tradisional. Analisis data menggunakan program SPSS. Analisis validitas menggunakan Product moment dari Karl Pearson dan analisis reliabilitas menggunakan Cronbach alpha. Hasil uji validitas menunjukkan bahwa 2 dari 6 item parameter pada aspek Hattra valid, 26 item dari 27 item parameter pada aspek cara perawatan valid, dan keseluruhan item dari 16 parameter pada aspek sarana valid. Hasil reliabilitas menunjukkan hasil yang reliabel. Pengembangan parameter penilaian keamanan pelayanan kesehatan tradisional empiris dihasilkan parameter reliabel dan sebagian besar parameter valid. Parameter yang tidak valid sebagian besar dilakukan penyesuaian kalimat tanpa mengubah makna.